2020
DOI: 10.1155/2020/8284504
|View full text |Cite
|
Sign up to set email alerts
|

Young and Older Adults Differ in Integration of Sensory Cues for Vertical Perception

Abstract: Introduction. The subjective visual vertical (SVV) measures the perception of a person’s spatial orientation relative to gravity. Weighted central integration of vestibular, visual, and proprioceptive inputs is essential for SVV perception. Without any visual references and minimal proprioceptive contribution, the static SVV reflects balance of the otolith organs. Normal aging is associated with bilateral and progressive decline in otolith organ function, but age-dependent effects on SVV are inconclusive. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
2
3
0
Order By: Relevance
“…However, the locomotive reactions, which are behaviorally reflected by variations in gait speed, are not fully understood. Herein we strengthen the notion that visual field dependency increases with aging 27,28 , this can be seen by (1) significant increase in the older adults group compared to the young group, and (2) only within the older adults, there is a significant correlation between age and rod and frame index. Future studies should measure visual field dependency across the lifespan to detect at which age the increase starts, and whether is plateaus eventually.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the locomotive reactions, which are behaviorally reflected by variations in gait speed, are not fully understood. Herein we strengthen the notion that visual field dependency increases with aging 27,28 , this can be seen by (1) significant increase in the older adults group compared to the young group, and (2) only within the older adults, there is a significant correlation between age and rod and frame index. Future studies should measure visual field dependency across the lifespan to detect at which age the increase starts, and whether is plateaus eventually.…”
Section: Discussionsupporting
confidence: 86%
“…figure 2, middle row). As older adults have increased reliance on visual cues 27,28 , an observation that was confirmed in our study as can be seen by the results of the rod and frame test (Figure 3) we expected to see larger speed modulations following virtually induced braking and exertion effect. Surprisingly, no significant difference was seen in the magnitude nor the timing of the peaks/troughs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Surprisingly, the diagnostic accuracy of these three questions was similar to those in the general population, with 80.7% accuracy, 78.7% sensitivity, and 87.2% specificity ( Wan et al, 2023 ). Originally, we expected less competent predictive ability of these parameters because hair cell and neuronal loss, a functional decline of the vestibular nerve, and reduced blood flow to the inner ear all contributed to an aging vestibular system ( Zalewski, 2015 ; Ji and Zhai, 2018 ; Abdul Razzak et al, 2020 ). These degenerative changes happen in the forms of decreased cervical/ocular vestibular-evoked myogenic potentials amplitudes and abnormal head impulse (HIT) and modified Romberg tests ( Davalos-Bichara and Agrawal, 2014 ; Fernández et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced multisensory integration in the elderly seems to be a good candidate for an explanation, with the potential mechanism such as increased time window of integration; deficits in top-down attention control enable more distraction by stimuli through sensory modalities, inverse effectiveness, and elevated background sensory processing baseline ( McGovern et al, 2014 ; Abdul Razzak et al, 2020 ). Similarly, Anson et al (2016) found that older adults exhibited significantly larger compensatory saccades relative to the young in the HIT test, which was used to evaluate the function of the three semicircular canals.…”
Section: Discussionmentioning
confidence: 99%